Effects of empathy and question types on suspects’ provision of information in investigative interviews - Baker-Eck, Bianca (International journal of police science & management, 2022)
The current study examines the relationship between the extent of, and various types of, empathy and of questions on suspects’ provision of information in 16 real-life police interviews. Multiple linear regressions were conducted to: predict suspects’ information provision in relation to (a) open questions, (b) the extent of displayed empathy and (c) each of the empathy types. Verbatim transcriptions of police interviews with suspects of sexual offences were coded for: (a) the extent and types of interviewer empathy, (b) the proportionality of interviewer open versus closed questions, and (c) suspects’ information provision. It was found that the proportion of open (versus closed) questions and the amount of empathy demonstrated by interviewers had a positive relationship with suspects’ information provision. The latter supports a recent finding by the authors involving a different sample of police interviews. Whereas in a growing number of countries the training of police interviewers has been emphasizing use of open questions, the current study aids weight to the small amount of research literature on the importance of interviewer empathy. Indeed, the effectiveness of open questions might be influenced by the amount of interviewer empathy in an interview.